Effectiveness of the Sukabumi Main Waste Bank (SAMMI) Program on Waste Prevention in Sukabumi City - Kinarsih Aprilida; M. Rijal Amirulloh; Dine Meigawati (Research Synergy Foundation, 2026)
Waste management has become a critical environmental issue in many regions, including Sukabumi City. To address this challenge, the Sukabumi City Environmental Agency (DLH) implemented the Sukabumi Main Waste Bank Program (SAMMI) as an effort to reduce waste volume directly at its source. This study was motivated by various challenges in the management of the SAMMI Program that affect its implementation effectiveness. The objective of this research is to analyze the effectiveness of the SAMMI Program in reducing waste in Sukabumi City using Nugroho’s Effectiveness Theory which encompasses five dimensions: policy accuracy, implementation accuracy, target accuracy, environmental accuracy, and process accuracy. This study employed a descriptive qualitative method, with data collected through interviews, observations, and documentation. The findings indicate that, in terms of implementation effectiveness, the SAMMI Program is supported by relevant policies, community involvement, and a waste savings system. Stakeholders perceive the program as beneficial in increasing community participation and awareness of waste sorting. However, measurable environmental outcomes remain limited, as city-level waste generation continued to increase. The program’s effectiveness has not been fully optimized due to limited waste processing facilities. Strengthening operational facilities, enhancing public education, and expanding partnerships are necessary to improve the program’s effectiveness and sustainability.